2019
DOI: 10.1002/lsm.23101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different 980‐nm Diode Laser Parameters in Hepatectomy

Abstract: Background and Objective: Despite the successful application of laser in animal experiments and clinics, the adjustment of laser parameters during surgery is still unclear. This study aimed to investigate the effect of different 980-nm diode laser parameters in hepatectomy. This could provide a clear protocol for using 980-nm diode laser in hepatectomy. Study Design/Materials and Methods: In total, 48 Sprague-Dawley rats were used to explore the effects of different 980-nm diode laser parameters in hepatectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In our previous study, we explored the effects of different 980-nm diode laser parameters in hepatectomy. 25 Based on this, the main observation indicators of the study were resection efficiency and thermal damage in different methods, including each area of the thermal damage zone, seeking a more reasonable and safe thermal damage control strategy. Thermal damage was evaluated using a histological specimen, hematoxylin-eosin (HE) stain, to obtain the thermal damage area of each zone.…”
Section: Observation Of Thermal Damagementioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we explored the effects of different 980-nm diode laser parameters in hepatectomy. 25 Based on this, the main observation indicators of the study were resection efficiency and thermal damage in different methods, including each area of the thermal damage zone, seeking a more reasonable and safe thermal damage control strategy. Thermal damage was evaluated using a histological specimen, hematoxylin-eosin (HE) stain, to obtain the thermal damage area of each zone.…”
Section: Observation Of Thermal Damagementioning
confidence: 99%
“…Water cooling is the continuous instillation of normal saline solution during a laser hepatectomy. Our previous studies demonstrated that thermal damage also increases with increasing laser output power 25 . Therefore, the output power should be adjusted to as low as possible to achieve similar cutting effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, various lasers such as CO 2 and Nd:YAG ones were utilized for medical treatment [7], [8]. It was also demonstrated that either continuous-wave (CW) or pulsed-mode lasers could be used for laser therapy [9], [10]. In clinical applications, short-pulse lasers represent the most commonly used therapeutic tool because they are able to damage the irradiated tissues without melting the surrounding before heat accumulation occurs [11].…”
Section: Introductionmentioning
confidence: 99%